Neurosyphilis with ocular involvement and normal magnetic resonance imaging results affirmed by metagenomic next-generation sequencing - Zhou, Xiaoli; Peng, Shengkun; Song, Tiange; Tie, Dandan; Tao, Xiaoyan; Jiang, Li; Zhang, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
The rapid and accurate identification of pathogenic agents is the key to guide clinicians on diagnosis and medication, especially for intractable diseases, such as neurosyphilis. It is extremely challenging for clinicians to diagnose neurosyphilis with no highly sensitive and specific test available. It is well known that the early transmission and immune evasion ability of Treponema pallidum have earned it the title of “stealth pathogen.” Neurosyphilis has complex clinical manifestations, including ocular involvement, which is infrequent and often overlooked, but its neuroimaging results may be normal. Therefore, it is important to find a new test that can detect the presence or absence of Treponema pallidum immediately for the diagnosis of neurosyphilis. We reviewed all the patients admitted to the Sichuan Provincial People’s Hospital between 2021 and 2022 who had ocular involvement and whose clinical samples were examined via metagenomic next-generation sequencing (mNGS), and we found 10 candidates for further analysis. The results of magnetic resonance imaging (MRI) were normal for four patients, and three of them met the diagnostic criteria for neurosyphilis confirmed by mNGS. In addition, the results of mNGS from the three patients were further validated using polymerase chain reaction (PCR). Five of the 10 patients had diplopia manifestations; two (20%) experienced abducens nerve palsies, two (20%) had eyelid drooping, and one (10%) had decreased vision. One of the 10 patients (10%) who was HIV positive and five patients had abnormal MRI results. To our knowledge, Treponema pallidum was detected by mNGS in patients with ocular involvement and normal MRI results for the first time. Given this situation, we recommend mNGS as a potential and supplementary tool for the diagnosis and differential diagnosis of neurosyphilis.